EFFECTIVENESS EVALUATION OF AUTOCLAVES AT NATIONAL INSTITUTE FOR CONTROL OF VACCINES AND BIOLOGICALS - Pham Thi Hang; Nguyen Thi Van Quynh; Nguyen Ky Anh; Le Viet Thanh (JOURNAL OF CONTROL VACCINES AND BIOLOGICALS, 2025)
National Institute for Control of Vaccines and Biologicals (NICVB) has utilized wet-heat sterilization methods for laboratory instruments, solution, and culture media. According to World Health Organization (WHO) recommendations, autoclaves used in sterilization processes require annual revalidation. Therefore, we conducted the study with the titled “Effectiveness Evaluation of Autoclaves at the National Institute for Control of Vaccines and Biologicals” to assess the operational performance and sterilization efficacy of autoclaves. The study was performed on two autoclaves: AC 10-TN and AC 11-TN. The results indicated that both autoclaves met operational performance requirements based on physical indicators, including: pressure ≥ 0.1 MPa, temperature ≥ 121°C, holding time ≥ 15 minutes and uniform heat distribution. Sterilization efficacy was also evaluated through biological indicators such as no appearance of microorganisms in both BI cultures and media that ensured sterility, while all positive controls met the required criteria and the risk of false negatives was eliminated. Consequently, both autoclaves were confirmed to be in high quality, reliable, and suitable for use in vaccine and biological product quality control testing.